Upaya Meningkatkan Kecerdasan Kinestetik Anak Melalui Outbound - Latifah Permatasari Fajrin; Eko Setiawan; Wulan Siti Hajar; Hery Setiyatna (UIN Raden Mas Said Surakarta, 2020)
The problem in this study is the low kinesthetic intelligence of children so that this study aims to improve children's kinesthetic intelligence through outbound. This research is a classroom action research (PTK). There are two subjects in this study, namely teachers and students. This research was conducted at TK Pilang 01, Masaran, Sragen in one cycle, during one meeting with 19 children. Collecting data through observation, interviews and documentation. The data analysis technique used includes descriptive analysis techniques, namely by comparing the pre-cycle with cycle 1. Performance indicators if the success reaches at least 65%, by calculating the percentage of the number of children who achieve development according to expectations / BSH & developing very well / BSB divided by the number of children multiplied by 100%. Based on the results of the study, it was found that the percentage of children's kinesthetic intelligence achievement who reached BSH and above was 31.58% in pre-cycle and experienced an increase in kinesthetic intelligence in cycle 1 of 84.21%. In conclusion, children's kinesthetic intelligence can be improved through Outbound.